+0  
 
0
250
1
avatar

-3(m-2)=21

Guest May 31, 2017
 #1
avatar+7266 
+1

-3(m - 2)   =   21

 

Divide both sides of the equation by   -3   .

m - 2   =   21 รท  -3

m - 2   =   -7

 

Add 2 to both sides of the equation.

m   =   -7 + 2

m   =   -5

hectictar  May 31, 2017

50 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.